2009
DOI: 10.1080/12265080902891818
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Strategies and Performances of Korean Firms: The Unified Theory of the Firm Perspective

Abstract: A good understanding of the nature of the firm is essential in developing corporate strategies, building corporate competitiveness, and establishing sound economic policy. Several theories have emerged on the nature of the firm: the neo-classical theory of the firm, the principal agency theory, the transaction cost theory, the property rights theory, the resource-based theory and the evolutionary theory. Each of these theories identify some elements that describe the nature of the firm, but no single theory is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The following studies, like Park et al . (2009), Kudlats et al (2014) and Hopkins and Ferguson (2014), show that the difference between average labor productivity and average labor cost is a statistically significant factor in firm performance.…”
Section: Resultsmentioning
confidence: 96%
“…The following studies, like Park et al . (2009), Kudlats et al (2014) and Hopkins and Ferguson (2014), show that the difference between average labor productivity and average labor cost is a statistically significant factor in firm performance.…”
Section: Resultsmentioning
confidence: 96%
“…Other scholar, such as Park, Shin and Jurn (2009) [3], on the contrary, stress on the importance of corporate strategy, state that certain aspects of strategic, such as the economy of scale, firm size, debt/equity ratio, and product range, can lead to profound influence on corporate performance. Hill [17], identified that R&D expenditure is positively related to profitability, while excessive diversification will bring passive influence on profitability.…”
Section: Corporate Strategymentioning
confidence: 99%
“…Previous researches indicated valid relation between corporate strategy and firm performance. (Porter, 1991 [2] ; Park, Shin and Jurn, 2009 [3] ). This article adopted quantitative analysis, taking three professional service firms as case studies.…”
mentioning
confidence: 99%
“…He highlighted the neoclassical theory that ownership and institutions neither affect the objective of firm nor its knowledge base, technology nor cost efficiency. Park and Shin (2004) believes the performance of the firm depends on technological advance, intellectual development and spirituality. Walker (2008) said that technological advance enhances the performance of firm by using incentive-system theory.…”
Section: Literature Reviewmentioning
confidence: 99%